2023
DOI: 10.1021/acsami.3c06183
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering of Low-Coordinated Metal–Organic Frameworks (MOFs) for Improved CO2 Access and Capture

Abstract: While metal−organic frameworks (MOFs) are promising gas adsorbents, their tortuous microporous structures cause additional resistance for gas diffusion, thus hindering the accessibility of interior active sites. Here, we present a practical strategy to incorporate missing cluster defects into a representative low-coordinated MOFs structure, Mg-MOF-74, while maintaining the stability of a defect-rich structure. In this proposed method, graphene oxide (GO) is employed as modulator, and crystallization time is va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Acetic acid can partially replace the organic ligand (dhtp) and bind to the interior metal nodes of the framework structure, thereby blocking the connections between the metal sites and the organic ligands and creating defects in that region. 57,58 X-ray photoelectron spectroscopy (XPS) confirmed the presence of defects in MOF-74-Co-0.46 eq. HOAc (Fig.…”
Section: Water-based Preparation Of Mof-74-co By High-gravity Technologymentioning
confidence: 93%
“…Acetic acid can partially replace the organic ligand (dhtp) and bind to the interior metal nodes of the framework structure, thereby blocking the connections between the metal sites and the organic ligands and creating defects in that region. 57,58 X-ray photoelectron spectroscopy (XPS) confirmed the presence of defects in MOF-74-Co-0.46 eq. HOAc (Fig.…”
Section: Water-based Preparation Of Mof-74-co By High-gravity Technologymentioning
confidence: 93%
“…Niu and co-workers found that graphene oxide could also be utilized as a modulator to alter the nucleation and growth of Mg-MOF-74 crystals, thus facilitating the formation of missing cluster defects. 119 At 298 K and 0.1 bar, the CO 2 uptake of the MOF@GO composite was enhanced by 19.29% due to the increased pore accessibility. Besides the modulator, changing the metal source has also been shown to introduce defects into MOFs.…”
Section: Pore Environment Engineering For Enhancing Co2 Affinitymentioning
confidence: 94%
“…3B). In addition, defect control in porous materials could also influence the pore structure with enhancements to the pore volume and surface area, 35–37 giving rise to a further boost in capacity.…”
Section: Flue Streams/biogasmentioning
confidence: 99%